On the effects of spreading sequence pairs over MIMO-STS systems. (2018) - Liu, Tianle; Alshabo, Ahmed; Stirling, David; Tran, Le Chung; Ros, Montserrat; Premaratne, Prashan; Vial, Peter James; Wysocki, Beata; Wysocki, Tad
Previous studies have found that the Multiple Access Interference (MAI) effect is strongly associated with which sequence pairs are spread over Multiple-Input Multiple-Output Space-Time Spreading (MIMO-STS) systems. An improved method of determining which sequence pairs are to be spread is proposed. The choice of these pairs from the selected spreading code families results in a number of ways to mitigate the MAI effects. A Software Defined Radio (SDR) test bed system has been developed to evaluate the selected spreading sequences, in an attempt to mitigate the MAI effects over 2 × 1 MIMO-STS systems. The SDR test bed results reveal that, for a number of the spreading sequence families, improved transmission properties for asynchronous transmission can be achieved.